2014
DOI: 10.1152/ajprenal.00262.2014
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase deficiency ameliorates progression of chronic kidney disease in mice

Abstract: Myeloperoxidase (MPO) is an enzyme expressed in neutrophils and monocytes/macrophages. Beside its well-defined role in innate immune defence, it may also be responsible for tissue damage. To identify the role of MPO in the progression of chronic kidney disease (CKD), we investigated CKD in a model of renal ablation in MPO knockout and wild-type mice. CKD was induced by 5/6 nephrectomy. Mice were followed for 10 wk to evaluate the impact of MPO deficiency on renal morbidity. Renal ablation induced CKD in wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…In the present study, we observed evidence of inflammation seven days after Nx (data not shown), corroborating earlier findings 7, 22, 39 . However, we chose to start our analysis fifteen days after renal ablation, when activation of inflammatory mechanisms could no longer be attributed to residual effects of surgical manipulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we observed evidence of inflammation seven days after Nx (data not shown), corroborating earlier findings 7, 22, 39 . However, we chose to start our analysis fifteen days after renal ablation, when activation of inflammatory mechanisms could no longer be attributed to residual effects of surgical manipulation.…”
Section: Discussionsupporting
confidence: 93%
“…Concomitant with these renal lesions, and even preceding them, the presence of inflammatory events such as infiltration by Mϕ and T-Ly was equally conspicuous. Previous studies reported even earlier activation of inflammatory mechanisms in the Nx model 1, 22, 39 , although the possibility that such response merely reflects the acute effect of surgical manipulation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 87%
“…Systolic blood pressure was measured with a computerized tail-cuff system (Process Control Blood Pressure 2900 series, TSE Systems, Bad Homburg, Germany), as previously described (16,18,22). Mice were placed into metabolic cages for a 6-h urine collection.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse-specific PCR primers were used. Levels of mRNA expression in each sample were normalized to 18S rRNA expression (15,18). Flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…Basal MMP-2 and inducible MMP-9 primarily degrade collagen and laminin, major components of ECM (28). Although insufficient MMP-2 and MMP-9 may lead to ECM accumulation, the expression levels of MMP-2 and MMP-9 in DN remain controversial (29).…”
Section: Discussionmentioning
confidence: 99%